Flagellar Basal Body Structural Proteins FlhB, FliM, and FliY Are Required for Flagellar-Associated Protein Expression in Listeria monocytogenes - Cheng, Changyong; Wang, Hang; Ma, Tiantian; Han, Xiao; Yang, Yongchun; Sun, Jing; Chen, Zhongwei; Yu, Huifei; Hang, Yi; Liu, Fengdan; Fang, Weihuan; Jiang, Lingli; et al. (Frontiers in Microbiology, 2018)
Listeria monocytogenes is a food-associated bacterium that is responsible for food-related illnesses worldwide. In the L. monocytogenes EGD-e genome, FlhB, FliM, and FliY (encoded by lmo0679, lmo0699, and lmo0700, respectively) are annotated as putative flagella biosynthesis factors, but their functions remain unknown. To explore whether FlhB, FliM, and FliY are involved in Listeria flagella synthesis, we constructed flhB, fliM, fliY, and other flagellar-related gene deletion mutants using a homologous recombination strategy. Then, we analyzed the motility, flagella synthesis, and protein expression of these mutant strains. Motility and flagella synthesis were completely abolished in the absence of flhB, fliM, or fliY. These impaired phenotypes were fully restored in the complemented strains CΔflhB, CΔfliM, and CΔfliY. The transcriptional levels of flagellar-related genes, including flaA, fliM, fliY, lmo0695, lmo0698, fliI, and fliS, were downregulated markedly in the absence of flhB, fliM, or fliY. Deletion of flhB resulted in the complete abolishment of FlaA expression, while it decreased FliM and FliY expression. The expression of FlaA was abolished completely in the absence of fliM or fliY. No significant changes were found in the expression of FlhF and two flagella synthesis regulatory factors, MogR and GmaR. We demonstrate for the first time that FlhB, FliM, and FliY not only mediate Listeria motility, but are also is involved in regulating flagella synthesis. This study provides novel insights that increase our understanding of the roles played by FlhB, FliM, and FliY in the flagellar type III secretion system in L. monocytogenes.